Collaborative Network Learning in Manufacturing - Quik, Wee Hock; Wright, Nevan J.; Rashid, Ammar; Herjanto, Halimin (International Journal of Advanced Corporate Learning (iJAC), 2014)
This study aims to investigate the antecedents of collaborative networked learning (CNL), to develop an integrative CNL framework and to bridge the gap between theory and praxis in manufacturing. It provides a holistic perspective of CNL within the complexity of the manufacturing environment, including empirical investigation using survey questionnaires. The findings and discussions draw upon socio-technical systems (STS) theory, and present the theoretical context and interpretations through the lens of manufacturing employees. Results of the study show the existence of significant positive influences of organizational support, promotive interactions, positive interdependence, internal-external learning, perceived effectiveness and perceived usefulness of CNL among manufacturing employees. The study offers a basis for empirical validity for measuring CNL in organizational learning, knowledge and information sharing in manufacturing.